1989
DOI: 10.1007/bf02028649
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic value of citicoline in the treatment of glaucoma (computerized and automated perimetric investigation)

Abstract: The favourable neurotrophic effects obtained by means of the intramuscular administration of citicoline, one of the intermediate compounds of phospholipids, on the visual field of patients suffering from open-angle glaucoma are referred. The drug was administered at the dose of 1 gm for ten consecutive days. Visual field was examined by means of central computerized perimetry and automated perimetry. All patients had well controlled intraocular pressure through beta-blockers, but presented characteristic glauc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 1 publication
0
30
0
Order By: Relevance
“…In particular, in a double-blind placebo-controlled study with glaucoma patients, citicoline given by intramuscular injections for 60 consecutive days has been found to shorten the visual evoked potential P100 latency and increase the N75-P100 amplitude [26]. In another study, perimetric improvement was observed following 10-day treatment with intramuscular injections of citicoline [31]. It has been concluded from these studies that citicoline improves visual pathway function in glaucoma and may be useful in the treatment of this disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, in a double-blind placebo-controlled study with glaucoma patients, citicoline given by intramuscular injections for 60 consecutive days has been found to shorten the visual evoked potential P100 latency and increase the N75-P100 amplitude [26]. In another study, perimetric improvement was observed following 10-day treatment with intramuscular injections of citicoline [31]. It has been concluded from these studies that citicoline improves visual pathway function in glaucoma and may be useful in the treatment of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a beneficial effect of citicoline has been described in a number of conditions affecting the visual system, like amblyopia [21,22,23,24] and nonarteritic ischemic optic neuropathy [25]. There are interesting findings concerning the use of citicoline in glaucoma [26,27,28,29,30,31]. In particular, in a double-blind placebo-controlled study with glaucoma patients, citicoline given by intramuscular injections for 60 consecutive days has been found to shorten the visual evoked potential P100 latency and increase the N75-P100 amplitude [26].…”
Section: Introductionmentioning
confidence: 99%
“…In two open studies with glaucoma patients (one of them with a long follow-up period), repeated intramuscular injections of this drug resulted in perimetric improvement [2,3], and in a double-blind placebo-controlled trial [4] such treatment led to the improved function of both retinal and postretinal visual pathways as assessed by electrophysiological techniques (visual-evoked potentials and pattern-reversed electroretinography). In amblyopia, intramuscular citicoline appeared to improve visual acuity, contrast sensitivity and visual-evoked potentials [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Although none of the recent reviews on citicoline (Weiss, 1995;Secades and Frontera, 1995;D'Orlando and Sandage, 1995) mentioned its possible application for treatment of glaucoma, a few clinical trials reported to date ahve indicated some benefits of such treatment (Pecori Giraldi et al, 1989;Parisi et al, 1999;Virno et al, 2000). The aim of the present review is to provide a rationale for further development of this drug for glaucoma treatment.…”
mentioning
confidence: 89%
“…Although the evidence for beneficial effects of citicoline in glaucoma is sparse, results of two long-term, open trials have been suggestive that this drug acts positively on the glaucomatous optic nerve damage as assessed perimetrically (Pecori Giraldi et al, 1989;Virno et al, 2000), and one short-term, placebo-controlled study indicated that such a treatment leads to functional improvement in both retinal and suprartetinal pathways (Parisi et al, 1999). Although these observations are not yet sufficient for the introduction of citicoline in standard therapy for glaucoma, they nicely correspond with welldocumented neuroprotective and dopamine-enhancing properties of the drug at the brain level.…”
Section: Concluding Commentsmentioning
confidence: 99%